High-temperature-resistant and high-strength aerogel heat-insulation composite material and preparation method thereof

By preparing high-strength aerogel thermal insulation composite materials, the problems of low compression strength and high thermal conductivity of traditional materials under low compression deformation are solved, and the demand for high-temperature and high-strength thermal insulation materials in the aerospace field is achieved. Lightweight, high strength, low thermal conductivity and good high temperature resistance.

CN119462067APending Publication Date: 2025-02-18CHANGSHA RONGLAN MACHINERY

Patent Information

Application Number
CN202411770995.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Traditional aerogel composites have low compression strength and high thermal conductivity under low compression deformation, making it difficult to meet the demand for high-temperature and high-strength thermal insulation materials in the aerospace field.

Method used

By configuring sol, sol impregnation, gel aging, supercritical drying and post-heat treatment, aerogel thermal insulation composite material with high strength, low thermal conductivity and good high temperature resistance was prepared.

Benefits of technology

It realizes the lightweight, high strength, low thermal conductivity and excellent high temperature resistance of composite materials, especially high compression strength under low deformation, and is suitable for aerospace and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462067A_ABST
    Figure CN119462067A_ABST
Patent Text Reader

Abstract

The invention discloses a high-temperature-resistant and high-strength aerogel heat insulation composite material and a preparation method thereof, and aims to solve the problems that a traditional aerogel composite material is low in strength and high in heat conductivity coefficient under low compression deformation in order to meet the strict requirements of the aerospace field for high-temperature-resistant and high-strength heat insulation materials. The prepared aerogel composite material has the characteristics of light weight, high strength, high temperature resistance and low heat conductivity coefficient, and has excellent mechanical strength under low deformation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aerogel thermal insulation composite materials, and specifically relates to a high-temperature resistant, high-strength aerogel thermal insulation composite material and a preparation method thereof. Background Art

[0002] New-type space vehicles fly in the atmosphere at high Mach numbers for a long time, and the fuselage is in a harsh environment such as severe startup heating, noise and vibration, and maneuvering flight overload impact. The large-area thermal insulation material of the fuselage should have the characteristics of high strength, excellent thermal insulation performance, high temperature resistance, and light weight.

[0003] There are some relevant studies: Chinese patent publication number CN113773044A uses long fibers as sutures to sew fiber fabrics and fiber felts to obtain fiber preforms, which are then compounded with sol to enhance the strength of aerogel composite materials. However, the compressive strength of the aerogel composite material at 10% deformation is only 0.78-1.22 MPa.

[0004] Chinese patent publication number CN116239817A uses a quartz fiber preform and a composite silicone aerogel, and obtains a high-strength, ablation-resistant silicone aerogel composite material by drying at room temperature and pressure, with a density of 0.3-0.8g / cm 3 , average pore size 40-200nm, tensile strength 5-25MPa, compressive strength 60-200MPa, thermal conductivity 0.03-0.06W / m·K, but the compressive strength under low deformation is not described, and it can be seen from the compression curve that the compressive strength under low deformation is low and the thermal conductivity is high, and the compressive strength under low compression deformation is one of the important parameters to characterize the strength of aerogel composite materials.

[0005] Chinese patent publication number CN118164777A uses a three-dimensional mesh structure preform with better compressive strength and skeleton stability than traditional fiber reinforcements. The compressive strength of the prepared aerogel composite material is 2.93-16.48MPa. Similarly, the compressive strength under low deformation is not described, and the compressive strength is low and the thermal conductivity is high.

[0006] Chinese patent publication number CN112592150A uses an inorganic ceramic fiber preform, mixes water-based alumina and water-based silica with the preform, and prepares an alumina-silica aerogel insulation composite material by a hydrothermal method. After a short-term heat treatment of 1800s at 1500°C, the material thickness shrinkage rate is less than 1.50%, but the compressive strength of the material under low deformation (3% strain) is only 0.12MPa, and the heat treatment time is short. The long-term temperature resistance of the material at 1500°C is unknown.

[0007] China Patent Publication No., uses inorganic ceramic fiber preforms to composite modified silica sol with inorganic aluminum and silicone as precursors, and obtains modified silica aerogel insulation composite materials after supercritical drying with ethanol. The shrinkage rate in the thickness direction is 1.2%-2.9% after 1100℃ / 1800s quartz lamp radiation heating treatment, but the stress corresponding to 3% deformation is only 0.10-0.55MPa, and the heat treatment time at this temperature is also short, which fails to reflect the long-term heat resistance at this temperature.

[0008] Aerogel thermal insulation materials have the characteristics of ultra-low thermal conductivity and light weight, but their low density and high porosity lead to poor mechanical properties. Therefore, improving the mechanical properties of aerogel materials and preparing high-strength aerogel thermal insulation materials to meet the stringent use requirements of new aerospace vehicles is one of the main research directions of aerogel thermal insulation materials. Summary of the invention

[0009] In response to the stringent demands for high-temperature resistant and high-strength thermal insulation materials in the aerospace field, the present invention provides a high-temperature resistant and high-strength aerogel thermal insulation composite material and a preparation method thereof, so as to solve the problems of low compression strength and high thermal conductivity of traditional aerogel composite materials under low compression deformation. The prepared aerogel composite material has the characteristics of light weight, high strength, high temperature resistance, low thermal conductivity, and high compression strength under low deformation.

[0010] The purpose of the present invention is achieved through the following technical solutions: A method for preparing a high-temperature resistant, high-strength aerogel thermal insulation composite material comprises the following steps: 1) Two-step method for preparing sol: In the first step, the silicon source, deionized water and acid catalyst are mixed and dissolved in an alcohol solvent, placed in a water bath at 30-60°C and stirred for 1-3 hours, and cooled to room temperature; In the second step, a mixed solution of an alkali catalyst, deionized water and an alcohol solvent is added and stirred to obtain a sol; The molar ratio of the silicon source, alcohol solvent, deionized water, acid catalyst and base catalyst is 1:(3-10):(4-12):(1.8×10 -3 -3.6×10 -3 ):(3.6×10 -2 -7.2×10 -2 ); The silicon source is ethyl silicate 40; The alcohol solvent is selected from methanol, ethanol, isopropanol and tert-butanol; The acid catalyst is selected from concentrated hydrochloric acid, concentrated nitric acid, and concentrated sulfuric acid; The alkaline catalyst is aqueous ammonia; 2) Sol impregnation: The fiber preform is clamped with a mold and placed in a vacuum environment, and the sol obtained in the previous step is sucked into the mold, and the pressure is maintained after the fiber preform is completely immersed; The fiber preform is made of fiber needle-punched blanket or woven, with a density of 0.15-0.40g / cm 3 , the fiber type is selected from quartz fiber, mullite fiber, and alumina fiber; The vacuum environment is -0.06 MPa~-0.1 MPa; The pressure holding time is 1-3h; 3) Gel and aging: Seal the mold obtained in the previous step and place it at 40-60°C for gel aging for 6-12 hours; 4) Supercritical drying: Place the mold obtained in the previous step into a supercritical drying kettle for drying. The supercritical temperature is 260-280°C, the pressure is 8-12 MPa, and the drying time is 4-8 hours. 5) Repeat steps 1) to 4) 1-3 times to in-situ reinforce the network skeleton in the mold to obtain an aerogel thermal insulation composite material; 6) Post-heat treatment: The prepared aerogel thermal insulation composite material is placed in an oven and heat treated at 600-800°C for 2 hours to obtain a high-temperature resistant and high-strength aerogel thermal insulation composite material with a designed density range of 0.45-0.88 g / cm 3 , the strength range under 3% compression deformation is 4.05-14.19 MPa, and the thermal conductivity at room temperature is 0.045-0.089 W / mK; the composite material is heat treated in a muffle furnace at 800-1000℃ for 2h, the mass loss rate is less than 1%, and the dimensional shrinkage rate in the thickness direction is less than 2.3%.

[0011] Furthermore, the alcohol solvent in step 1) is selected from ethanol; and the acid catalyst is selected from concentrated hydrochloric acid.

[0012] The present invention also relates to a high-temperature resistant, high-strength aerogel thermal insulation composite material, which is obtained by the preparation method of the high-temperature resistant, high-strength aerogel thermal insulation composite material. The density and structural strength of the composite material can be designed according to application requirements, and the design density range is 0.45-0.88 g / cm 3 The composite material has a strength range of 4.05-14.19 MPa under 3% compression deformation, and the thermal conductivity at room temperature is in the range of 0.045-0.089 W / mK, which has a good heat insulation effect; the composite material has good high temperature resistance. The prepared composite material is placed in a muffle furnace for heat treatment at 800-1000℃ for 2h, the mass loss rate is less than 1%, and the dimensional shrinkage rate in the thickness direction is less than 2.3%, which has excellent high temperature resistance.

[0013] Compared with the prior art, the present invention has the following advantages: 1. The method for preparing a high-temperature resistant and high-strength aerogel thermal insulation composite material described in the present invention adopts ethyl silicate 40 as a silicon source, designs the fiber type and density of the fiber preform and the molar ratio of the silicon source, regulates the mass fraction of silicon dioxide generated in the sol, and strengthens the porous network skeleton of silicon dioxide through repeated impregnation and supercritical drying, and post-heat treatment, thereby significantly improving the structural strength of the composite material and effectively improving the problem of low compressive strength under low compression deformation.

[0014] 2. The high temperature resistant and high strength aerogel thermal insulation composite material of the present invention has a designable density and structural strength. The composite material preparation method can be designed to have a density range of 0.45-0.88 g / cm according to application requirements. 3 , the composite material has a strength range of 4.05-14.19 MPa under 3% compression deformation, and the thermal conductivity at room temperature is only in the range of 0.045-0.089 W / mK, which has a good thermal insulation effect and greatly broadens the application of aerogel materials in aerospace, new energy, petroleum and other fields.

[0015] 3. The high-temperature resistant and high-strength aerogel thermal insulation composite material of the present invention has good high-temperature resistance. The prepared composite material is placed in a muffle furnace for heat treatment at 1000°C for 2h, and the mass loss rate is less than 1%, and the dimensional shrinkage rate in the thickness direction is less than 2.3%. It has excellent high-temperature resistance and has broad application prospects in the field of high-temperature resistant thermal insulation materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a process flow chart of a method for preparing a high temperature resistant, high strength aerogel thermal insulation composite material according to the present invention; Figure 2 is a stress-strain curve of a compressive strength test of a high-temperature resistant, high-strength aerogel thermal insulation composite material obtained in Example 4 of the present invention; Figure 3 This is a comparison of the appearance of a high-temperature resistant, high-strength aerogel thermal insulation composite material prepared in Example 7 of the present invention before and after heat treatment in a muffle furnace at 1000° C. for 2 hours (before heat treatment); Figure 4 This is a comparison diagram of the appearance of a high-temperature resistant, high-strength aerogel thermal insulation composite material prepared in Example 7 of the present invention before and after heat treatment at 1000° C. for 2 hours in a muffle furnace (after heat treatment). DETAILED DESCRIPTION

[0017] The present invention is further described in detail below by way of examples, but these examples should not be considered as limiting the present invention.

[0018] In the embodiments and comparative examples: Density data is measured according to GB / T 17911-2006; The compressive strength is measured according to GB / T 13480-2014; The room temperature thermal conductivity data is measured according to GB / T 10295-2008; Embodiment 1: A method for preparing a high-temperature resistant, high-strength aerogel thermal insulation composite material comprises the following steps: 1) Two-step method for preparing sol: In the first step, the silicon source, deionized water and acid catalyst are mixed and dissolved in an alcohol solvent, placed in a 40°C water bath and stirred for 2 hours, and cooled to room temperature; in the second step, a mixed solution of an alkali catalyst, deionized water and alcohol solvent is added and stirred to obtain a sol; The molar ratio of the silicon source, alcohol solvent, deionized water, acid catalyst and base catalyst is 1:6:12:1.8×10 -3 :3.6×10 -2 ; The silicon source is ethyl silicate 40; The alcohol solvent is selected from ethanol; The acid catalyst is selected from concentrated hydrochloric acid; The alkaline catalyst is aqueous ammonia; 2) Sol impregnation: The fiber preform is clamped with a mold and placed in a vacuum environment, and the sol obtained in the previous step is sucked into the mold, and the pressure is maintained after the fiber preform is completely immersed; The fiber preform has a density of 0.20 g / cm 3 , made of fibers, the fiber type is selected from alumina fiber needle-punched blanket; The vacuum environment is -0.1 MPa; The pressure holding time is 1h; 3) Gel and aging: The mold obtained in the previous step was sealed and placed at 60°C for gel aging for 6 hours; 4) Supercritical drying: The mold obtained in the previous step is placed in a supercritical drying kettle for drying. The supercritical temperature is 280°C, the pressure is 12MPa, and the drying time is 8h. 5) Repeat steps 1) to 4) twice to in-situ reinforce the network skeleton in the mold to obtain an aerogel thermal insulation composite material; 6) Post-heat treatment: The prepared aerogel thermal insulation composite material was placed in an oven and heat treated at 600°C for 2 h to obtain a high-temperature resistant and high-strength aerogel thermal insulation composite material with a density of 0.66 g / cm 3, the strength under 3% compression deformation is 4.95 MPa, and the thermal conductivity at room temperature is 0.067 W / mK; the composite material is heat treated in a muffle furnace at 1000℃ for 2h, the mass loss rate is 0.57%, and the dimensional shrinkage rate in the thickness direction is 2.3%.

[0019] Embodiment 2: A method for preparing a high-temperature resistant, high-strength aerogel thermal insulation composite material comprises the following steps: 1) Two-step method for preparing sol: In the first step, the silicon source, deionized water and acid catalyst are mixed and dissolved in an alcohol solvent, placed in a 40°C water bath and stirred for 1 hour, and cooled to room temperature; in the second step, a mixed solution of a base catalyst, deionized water and alcohol solvent is added and stirred to obtain a sol; The molar ratio of the silicon source, alcohol solvent, deionized water, acid catalyst and base catalyst is 1:10:10:3.6×10 -3 :5.4×10 -2 ; The silicon source is ethyl silicate 40; The alcohol solvent is selected from isopropanol; The acid catalyst is selected from concentrated sulfuric acid; The alkaline catalyst is aqueous ammonia; 2) Sol impregnation: The fiber preform is clamped with a mold and placed in a vacuum environment, and the sol obtained in the previous step is sucked into the mold, and the pressure is maintained after the fiber preform is completely immersed; The fiber preform has a density of 0.25 g / cm 3 , made of fiber, the fiber type is selected from mullite fiber needle-punched blanket; The vacuum environment is -0.06 MPa; The pressure holding time is 3h; 3) Gel and aging: The mold obtained in the previous step was sealed and placed at 40°C for gel aging for 12 hours; 4) Supercritical drying: The mold obtained in the previous step is placed in a supercritical drying kettle for drying. The supercritical temperature is 260°C, the pressure is 10MPa, and the drying time is 6h. 5) Repeat steps 1) to 4) twice to in-situ reinforce the network skeleton in the mold to obtain an aerogel thermal insulation composite material; 6) Post-heat treatment: The prepared aerogel thermal insulation composite material was placed in an oven and heat treated at 600°C for 2 h to obtain a high-temperature resistant and high-strength aerogel thermal insulation composite material with a density of 0.73 g / cm 3, the strength under 3% compression deformation is 7.36 MPa, and the thermal conductivity at room temperature is 0.074 W / mK; the composite material is heat treated in a muffle furnace at 1000℃ for 2h, the mass loss rate is 0.78%, and the dimensional shrinkage rate in the thickness direction is 0.19%.

[0020] Embodiment 3: A method for preparing a high-temperature resistant, high-strength aerogel thermal insulation composite material comprises the following steps: 1) Two-step method for preparing sol: In the first step, the silicon source, deionized water and acid catalyst are mixed and dissolved in an alcohol solvent, placed in a 60°C water bath and stirred for 3 hours, and cooled to room temperature; in the second step, a mixed solution of an alkali catalyst, deionized water and alcohol solvent is added and stirred to obtain a sol; The molar ratio of the silicon source, alcohol solvent, deionized water, acid catalyst and base catalyst is 1:8:10:3.6×10 -3 :7.2×10 -2 ; The silicon source is ethyl silicate 40; The alcohol solvent is selected from tert-butyl alcohol; The acid catalyst is selected from concentrated sulfuric acid; The alkaline catalyst is aqueous ammonia; 2) Sol impregnation: The fiber preform is clamped with a mold and placed in a vacuum environment, and the sol obtained in the previous step is sucked into the mold, and the pressure is maintained after the fiber preform is completely immersed; The fiber preform has a density of 0.20 g / cm 3 , made of fiber, the fiber type is selected from mullite fiber needle-punched blanket; The vacuum environment is -0.08 MPa; The pressure holding time is 2h; 3) Gel and aging: The mold obtained in the previous step is sealed and placed at 60°C for gel aging for 8 hours; 4) Supercritical drying: The mold obtained in the previous step is placed in a supercritical drying kettle for drying. The supercritical temperature is 260°C, the pressure is 8MPa, and the drying time is 4h. 5) Repeat steps 1) to 4) once to in-situ reinforce the network skeleton in the mold to obtain an aerogel thermal insulation composite material; 6) Post-heat treatment: The prepared aerogel thermal insulation composite material was placed in an oven and heat treated at 800°C for 2 h to obtain a high-temperature resistant and high-strength aerogel thermal insulation composite material with a density of 0.45 g / cm 3, the strength under 3% compression deformation is 4.05 MPa, and the thermal conductivity at room temperature is 0.045 W / mK; the composite material is heat treated in a muffle furnace at 1000℃ for 2h, the mass loss rate is 0.69%, and the dimensional shrinkage rate in the thickness direction is 1.84%.

[0021] Embodiment 4: A method for preparing a high-temperature resistant, high-strength aerogel thermal insulation composite material comprises the following steps: 1) Two-step method for preparing sol: In the first step, the silicon source, deionized water and acid catalyst are mixed and dissolved in an alcohol solvent, placed in a 40°C water bath and stirred for 2 hours, and cooled to room temperature; in the second step, a mixed solution of an alkali catalyst, deionized water and alcohol solvent is added and stirred to obtain a sol; The molar ratio of the silicon source, alcohol solvent, deionized water, acid catalyst and base catalyst is 1:7:12:1.8×10 -3 :3.6×10 -2 ; The silicon source is ethyl silicate 40; The alcohol solvent is selected from ethanol; The acid catalyst is selected from concentrated nitric acid; The alkaline catalyst is aqueous ammonia; 2) Sol impregnation: The fiber preform is clamped with a mold and placed in a vacuum environment, and the sol obtained in the previous step is sucked into the mold, and the pressure is maintained after the fiber preform is completely immersed; The fiber preform has a density of 0.15 g / cm 3 , it is made of fiber, and the fiber type is selected from quartz fiber woven parts; The vacuum environment is -0.1 MPa; The pressure holding time is 3h; 3) Gel and aging: The mold obtained in the previous step is sealed and placed at 60°C for gel aging for 8 hours; 4) Supercritical drying: The mold obtained in the previous step is placed in a supercritical drying kettle for drying. The supercritical temperature is 280°C, the pressure is 12MPa, and the drying time is 8h. 5) Repeat steps 1) to 4) 3 times to in-situ reinforce the network skeleton in the mold to obtain an aerogel thermal insulation composite material; 6) Post-heat treatment: The prepared aerogel thermal insulation composite material was placed in an oven and heat treated at 800°C for 2 h to obtain a high-temperature resistant and high-strength aerogel thermal insulation composite material with a density of 0.84 g / cm 3, the strength under 3% compression deformation is 11.28 MPa, and the thermal conductivity at room temperature is 0.085 W / mK; the composite material is heat treated in a muffle furnace at 1000℃ for 2h, the mass loss rate is 0.88%, and the dimensional shrinkage rate in the thickness direction is 0.56%.

[0022] Embodiment 5: A method for preparing a high-temperature resistant, high-strength aerogel thermal insulation composite material comprises the following steps: 1) Two-step method for preparing sol: In the first step, the silicon source, deionized water and acid catalyst are mixed and dissolved in an alcohol solvent, placed in a 40°C water bath and stirred for 2 hours, and cooled to room temperature; in the second step, a mixed solution of an alkali catalyst, deionized water and alcohol solvent is added and stirred to obtain a sol; The molar ratio of the silicon source, alcohol solvent, deionized water, acid catalyst and base catalyst is 1:7:12:3.6×10 -3 :7.2×10 -2 ; The silicon source is ethyl silicate 40; The alcohol solvent is selected from ethanol; The acid catalyst is selected from concentrated nitric acid; The alkaline catalyst is aqueous ammonia; 2) Sol impregnation: The fiber preform is clamped with a mold and placed in a vacuum environment, and the sol obtained in the previous step is sucked into the mold, and the pressure is maintained after the fiber preform is completely immersed; The fiber preform has a density of 0.32 g / cm 3 , it is made of fiber, and the fiber type is selected from quartz fiber woven parts; The vacuum environment is -0.1 MPa; The pressure holding time is 3h; 3) Gel and aging: The mold obtained in the previous step was sealed and placed at 40°C for gel aging for 12 hours; 4) Supercritical drying: The mold obtained in the previous step is placed in a supercritical drying kettle for drying. The supercritical temperature is 280°C, the pressure is 12MPa, and the drying time is 8h. 5) Repeat steps 1) to 4) once to in-situ reinforce the network skeleton in the mold to obtain an aerogel thermal insulation composite material; 6) Post-heat treatment: The prepared aerogel thermal insulation composite material was placed in an oven and heat treated at 800°C for 2 h to obtain a high-temperature resistant and high-strength aerogel thermal insulation composite material with a density of 0.55 g / cm 3, the strength under 3% compression deformation is 8.03 MPa, and the thermal conductivity at room temperature is 0.055 W / mK; the composite material is heat treated in a muffle furnace at 1000℃ for 2h, the mass loss rate is 0.12%, and the dimensional shrinkage rate in the thickness direction is 1.56%.

[0023] Embodiment 6: A method for preparing a high-temperature resistant, high-strength aerogel thermal insulation composite material comprises the following steps: 1) Two-step method for preparing sol: In the first step, the silicon source, deionized water and acid catalyst are mixed and dissolved in an alcohol solvent, placed in a 60°C water bath and stirred for 2 hours, and cooled to room temperature; in the second step, a mixed solution of an alkali catalyst, deionized water and alcohol solvent is added and stirred to obtain a sol; The molar ratio of the silicon source, alcohol solvent, deionized water, acid catalyst and base catalyst is 1:6:6:3.6×10 -3 :5.4×10 -2 ; The silicon source is ethyl silicate 40; The alcohol solvent is selected from ethanol; The acid catalyst is selected from concentrated nitric acid; The alkaline catalyst is aqueous ammonia; 2) Sol impregnation: The fiber preform is clamped with a mold and placed in a vacuum environment, and the sol obtained in the previous step is sucked into the mold, and the pressure is maintained after the fiber preform is completely immersed; The fiber preform has a density of 0.15 g / cm 3 , made of fiber, the fiber type is selected from mullite fiber needle-punched blanket; The vacuum environment is -0.06 MPa; The pressure holding time is 1h; 3) Gel and aging: The mold obtained in the previous step was sealed and placed at 60°C for gel aging for 6 hours; 4) Supercritical drying: The mold obtained in the previous step is placed in a supercritical drying kettle for drying. The supercritical temperature is 280°C, the pressure is 12MPa, and the drying time is 8h. 5) Repeat steps 1) to 4) twice to in-situ reinforce the network skeleton in the mold to obtain an aerogel thermal insulation composite material; 6) Post-heat treatment: The prepared aerogel thermal insulation composite material was placed in an oven and heat treated at 600°C for 2 h to obtain a high-temperature resistant and high-strength aerogel thermal insulation composite material with a density of 0.73 g / cm 3, the strength under 3% compression deformation is 6.35 MPa, and the thermal conductivity at room temperature is 0.074 W / mK; the composite material is heat treated in a muffle furnace at 1000℃ for 2h, the mass loss rate is 0.98%, and the dimensional shrinkage rate in the thickness direction is 0.25%.

[0024] Embodiment 7: A method for preparing a high-temperature resistant, high-strength aerogel thermal insulation composite material comprises the following steps: 1) Two-step method for preparing sol: In the first step, the silicon source, deionized water and acid catalyst are mixed and dissolved in an alcohol solvent, placed in a 60°C water bath and stirred for 2 hours, and cooled to room temperature; in the second step, a mixed solution of an alkali catalyst, deionized water and alcohol solvent is added and stirred to obtain a sol; The molar ratio of the silicon source, alcohol solvent, deionized water, acid catalyst and base catalyst is 1:3:4:3.6×10 -3 :7.2×10 -2 ; The silicon source is ethyl silicate 40; The alcohol solvent is selected from ethanol; The acid catalyst is selected from concentrated nitric acid; The alkaline catalyst is aqueous ammonia; 2) Sol impregnation: The fiber preform is clamped with a mold and placed in a vacuum environment, and the sol obtained in the previous step is sucked into the mold, and the pressure is maintained after the fiber preform is completely immersed; The fiber preform has a density of 0.22 g / cm 3 , it is made of fiber, and the fiber type is selected from quartz fiber woven parts; The vacuum environment is -0.1 MPa; The pressure holding time is 3h; 3) Gel and aging: The mold obtained in the previous step was sealed and placed at 40°C for gel aging for 12 hours; 4) Supercritical drying: The mold obtained in the previous step is placed in a supercritical drying kettle for drying. The supercritical temperature is 280°C, the pressure is 12MPa, and the drying time is 8h. 5) Repeat steps 1) to 4) twice to in-situ reinforce the network skeleton in the mold to obtain an aerogel thermal insulation composite material; 6) Post-heat treatment: The prepared aerogel thermal insulation composite material was placed in an oven and heat treated at 1000°C for 2 h to obtain a high-temperature resistant and high-strength aerogel thermal insulation composite material with a density of 0.88 g / cm 3, the strength under 3% compression deformation is 14.19 MPa, and the thermal conductivity at room temperature is 0.089 W / mK; the composite material is heat treated in a muffle furnace at 1000℃ for 2h, the mass loss rate is 0.92%, and the dimensional shrinkage rate in the thickness direction is 0.07%.

[0025] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that different silicon sources are used. Example 1 uses 40 ethyl silicate, while Comparative Example 1 uses 28 ethyl silicate. The preparation method of Comparative Example 1 comprises the following steps: 1) Two-step method for preparing sol: In the first step, the silicon source, deionized water and acid catalyst are mixed and dissolved in an alcohol solvent, placed in a 40°C water bath and stirred for 2 hours, and cooled to room temperature; in the second step, a mixed solution of an alkali catalyst, deionized water and alcohol solvent is added and stirred to obtain a sol; The molar ratio of the silicon source, alcohol solvent, deionized water, acid catalyst and base catalyst is 1:6:12:1.8×10 -3 :3.6×10 -2 ; The silicon source is ethyl silicate 28; The alcohol solvent is selected from ethanol; The acid catalyst is selected from concentrated hydrochloric acid; The alkaline catalyst is aqueous ammonia; 2) Sol impregnation: The fiber preform is clamped with a mold and placed in a vacuum environment, and the sol obtained in the previous step is sucked into the mold, and the pressure is maintained after the fiber preform is completely immersed; The fiber preform has a density of 0.20 g / cm 3 , made of fibers, the fiber type is selected from alumina fiber needle-punched blanket; The vacuum environment is -0.1 MPa; The pressure holding time is 1h; 3) Gel and aging: The mold obtained in the previous step was sealed and placed at 60°C for gel aging for 6 hours; 4) Supercritical drying: The mold obtained in the previous step is placed in a supercritical drying kettle for drying. The supercritical temperature is 280°C, the pressure is 12MPa, and the drying time is 8h. 5) Repeat steps 1) to 4) twice to in-situ reinforce the network skeleton in the mold to obtain an aerogel thermal insulation composite material; 6) Post-heat treatment: The prepared aerogel thermal insulation composite material was placed in an oven and heat treated at 600°C for 2 h to obtain a high-temperature resistant and high-strength aerogel thermal insulation composite material with a density of 0.36 g / cm 3, the strength under 3% compression deformation is 0.55 MPa, and the thermal conductivity at room temperature is 0.048 W / mK; the composite material is heat treated in a muffle furnace at 1000℃ for 2h, the mass loss rate is 8.45%, and the dimensional shrinkage rate in the thickness direction is 15.12%.

[0026] Comparative Example 2: The difference between Comparative Example 2 and Example 7 lies in the different silicon sources used, the number of immersion times and the post-heat treatment temperature; The preparation method of Comparative Example 2 comprises the following steps: 1) Two-step method for preparing sol: In the first step, the silicon source, deionized water and acid catalyst are mixed and dissolved in an alcohol solvent, placed in a 40°C water bath and stirred for 2 hours, and cooled to room temperature; in the second step, a mixed solution of an alkali catalyst, deionized water and alcohol solvent is added and stirred to obtain a sol; The molar ratio of the silicon source, alcohol solvent, deionized water, acid catalyst and base catalyst is 1:3:4:3.6×10 -3 :7.2×10 -2 ; The silicon source is ethyl silicate 40; The alcohol solvent is selected from ethanol; The acid catalyst is selected from concentrated hydrochloric acid; The alkaline catalyst is aqueous ammonia; 2) Sol impregnation: The fiber preform is clamped with a mold and placed in a vacuum environment, and the sol obtained in the previous step is sucked into the mold, and the pressure is maintained after the fiber preform is completely immersed; The fiber preform has a density of 0.22 g / cm 3 , it is made of fiber, and the fiber type is selected from quartz fiber woven parts; The vacuum environment is -0.1 MPa; The pressure holding time is 3h; 3) Gel and aging: The mold obtained in the previous step was sealed and placed at 40°C for gel aging for 12 hours; 4) Supercritical drying: The mold obtained in the previous step is placed in a supercritical drying kettle for drying. The supercritical temperature is 280°C, the pressure is 12MPa, and the drying time is 8h. 5) Post-heat treatment: The prepared aerogel thermal insulation composite material was placed in an oven and heat treated at 800°C for 2 h to obtain a high-temperature resistant and high-strength aerogel thermal insulation composite material with a density of 0.34 g / cm 3 , the strength under 3% compression deformation is 0.82 MPa, and the thermal conductivity at room temperature is 0.046 W / mK; the composite material is heat treated in a muffle furnace at 1000℃ for 2h, the mass loss rate is 5.6%, and the dimensional shrinkage rate in the thickness direction is 9.38%.

[0027] Table 1: Properties of the composite materials obtained in the examples and comparisons

[0028] The results in Table 1 show that: 1. It can be seen from Examples 1-7 that the method for preparing a high-temperature resistant, high-strength aerogel thermal insulation composite material of the present invention is to obtain a high-temperature resistant, high-strength aerogel thermal insulation composite material by designing the fiber type and density of the fiber preform and the molar ratio of the silicon source and regulating the mass fraction of the silicon dioxide generated in the sol. The designed density range of the composite material is 0.45-0.88 g / cm 3 , the strength range is 4.05-14.19 MPa under 3% compression deformation, and the thermal conductivity at room temperature is 0.045-0.089 W / mK; the composite material is heat treated in a muffle furnace at 800-1000℃ for 2h, with a mass loss rate of 0.12-0.98% and a dimensional shrinkage rate in the thickness direction of 0.07-2.3%. It has a good thermal insulation effect and excellent high temperature resistance.

[0029] 2. By comparing Example 1 with Comparative Example 1, it is shown that the composite material prepared by using ethyl silicate 40 has higher compressive strength and high temperature resistance under low deformation, and the composite material has excellent properties of low density and low thermal conductivity.

[0030] 3. By comparing Example 7 with Comparative Example 2, it is shown that by repeated impregnation and supercritical drying, and in-situ strengthening of the porous silica network skeleton by post-heat treatment, the structural strength of the composite material can be significantly improved, and the problem of low compressive strength under low compression deformation can be effectively improved.

[0031] The above are only preferred implementations of the present invention. The protection scope of the present invention is not limited to the above embodiments. Various process schemes that are not substantially different from the concept of the present invention are within the protection scope of the present invention.

Claims

1. A method for preparing a high temperature resistant, high strength aerogel thermal insulation composite material, characterized in that: The following steps are involved: 1) Two-step method for preparing sol: In the first step, the silicon source, deionized water and acid catalyst are mixed and dissolved in an alcohol solvent, placed in a water bath at 30-60°C and stirred for 1-3 hours, and cooled to room temperature; In the second step, a mixed solution of an alkali catalyst, deionized water and an alcohol solvent is added and stirred to obtain a sol; The molar ratio of the silicon source, alcohol solvent, deionized water, acid catalyst and base catalyst is 1:(3-10):(4-12):(1.8×10 -3 -3.6×10 -3 ):(3.6×10 -2 -7.2×10 -2 ); The silicon source is ethyl silicate 40; The alcohol solvent is selected from methanol, ethanol, isopropanol and tert-butanol; The acid catalyst is selected from concentrated hydrochloric acid, concentrated nitric acid, and concentrated sulfuric acid; The alkaline catalyst is aqueous ammonia; 2) Sol impregnation: The fiber preform is clamped with a mold and placed in a vacuum environment, and the sol obtained in the previous step is sucked into the mold, and the pressure is maintained after the fiber preform is completely immersed; The fiber preform is made of fiber needle-punched blanket or woven, with a density of 0.15-0.40g / cm 3 , the fiber type is selected from quartz fiber, mullite fiber, and alumina fiber; The vacuum environment is -0.06 MPa~-0.1 MPa; The pressure holding time is 1-3h; 3) Gel and aging: Seal the mold obtained in the previous step and place it at 40-60°C for gel aging for 6-12 hours; 4) Supercritical drying: Place the mold obtained in the previous step into a supercritical drying kettle for drying. The supercritical temperature is 260-280°C, the pressure is 8-12 MPa, and the drying time is 4-8 hours. 5) Repeat steps 1) to 4) 1-3 times to in-situ reinforce the network skeleton in the mold to obtain an aerogel thermal insulation composite material; 6) Post-heat treatment: The prepared aerogel thermal insulation composite material is placed in an oven and heat treated at 600-800°C for 2 hours to obtain a high-temperature resistant and high-strength aerogel thermal insulation composite material with a designed density range of 0.45-0.88 g / cm 3 , the strength range under 3% compression deformation is 4.05-14.19 MPa, and the thermal conductivity at room temperature is 0.045-0.089 W / mK; the composite material is heat treated in a muffle furnace at 800-1000℃ for 2h, the mass loss rate is less than 1%, and the dimensional shrinkage rate in the thickness direction is less than 2.3%.

2. The method for preparing a high temperature resistant, high strength aerogel thermal insulation composite material according to claim 1, characterized in that: The alcohol solvent in step 1) is selected from ethanol; the acid catalyst is selected from concentrated hydrochloric acid.

3. A high temperature resistant, high strength aerogel thermal insulation composite material, characterized by: The composite material is obtained by the preparation method of a high temperature resistant and high strength aerogel thermal insulation composite material according to claim 1 or 2, wherein the design density of the composite material is in the range of 0.45-0.88 g / cm 3 , a composite material with a strength range of 4.05-14.19 MPa under 3% compression deformation, and a thermal conductivity of 0.045-0.089 W / mK at room temperature; the composite material is placed in a muffle furnace for heat treatment at 800-1000°C for 2h, the mass loss rate is less than 1%, and the dimensional shrinkage rate in the thickness direction is less than 2.3%.

Citation Information

Patent Citations

  • Preparation method of aluminum oxide-silicon oxide aerogel thermal insulation composite material

    CN112592150A

  • High-strength aerogel composite material and preparation method thereof

    CN113773044A

  • High-strength ablation-resistant nanopore organic silicon aerogel composite material as well as preparation method and application thereof

    CN116239817A

  • Aerogel composite material, preparation method thereof and thermal insulation material

    CN118164777A

Cited By

  • Organic silicon aerogel composite material as well as preparation method and application thereof

    CN120590680A